Cancer detection and management in patients with haemophilia: a retrospective European multicentre study. (6th August 2013) - Biron‐Andreani, C.; de, P.; D'oiron, R.; Chambost, H.; Schved, J.‐F.; Hermans, C.
Summary Lymphomas or hepatocarcinomas related to blood‐borne transmitted diseases are well‐known malignancies in persons with haemophilia (PWH). However, rising life expectancy has increased the number of PWH suffering from other malignancies. This study aimed to collect cancer occurrence data in PWH followed in five European haemophilia treatment centres (Brussels, Geneva, Marseille, Montpellier and Paris‐Bicêtre) over the last 10 years and to analyse some particular features of cancer occurring in PWH. In total, 45 malignancies were diagnosed in 1067 PWH. The most common malignancies were hepatocellular carcinoma (12/45) and urogenital tract tumours (9/45). Bleeding at presentation or changes in bleeding pattern was indicative of cancer in four patients. Three patients with mild haemophilia developed anti‐factor VIII inhibitors after intensive substitution therapy prior to surgery or invasive procedures. There was no bleeding associated with chemotherapy or radiotherapy. A few bleeding complications occurred following invasive (3/39) or surgical procedures (2/27) as a result of insufficient hemostatic coverage or in spite of adequate substitution. No bleeding was noted after liver or prostate biopsies. Following cancer diagnosis, five patients were switched from on‐demand to prolonged prophylaxis substitution. In the majority of cases, the standard cancer treatment protocol was not modified on account of concomitant haemophilia. Thus, oncological treatments are not contraindicated and should not be withheld in PWH assuming that adequate haemostasis correction is undertaken. As shown by our study results, a change in bleeding pattern in adult PWH should raise suspicion of a malignancy. Intensive substitution must be considered a risk factor for inhibitor development.